Implementation of Problem-Based Learning Methods to Improve Fiqh Learning Achievement of Zakat Material in Grade V MIN 8 South Jakarta Students for the 2022/2023 Academic Year - Mualimah Mualimah (Journal of Social Research, 2024)
This research is based on the following problems: (a) Does the learning method of Problem Based Learning affect the learning outcomes of Fiqh in Class V Students? (b) How high is the level of mastery of Fiqh subject matter with the application of the Problem Based Learning learning method to Class V students? The objectives of this study are: (a) To reveal the influence of learning Problem Based Learning methods on Fiqh learning outcomes in Class V Students. (b) Want to know how far the understanding and mastery of Fiqh subjects after the application of the Problem Based Learning learning method in Class V students. Each round consists of four stages: design, activity and observation, reflection, and reference. The target of this study was Class V students. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (66%), cycle II (75%), cycle III (100%). The conclusion of this study is that the Problem Based Learning learning method method can have a positive effect on the learning motivation of Class V students, and this learning model can be used as an alternative to Fiqh.